Oligomeric structure of the human immunodeficiency virus type 1 envelope glycoprotein. - Earl, P L (1990)
The envelope (env) glycoprotein of human immunodeficiency virus type 1 (HIV-1) consists of two noncovalently associated subunits, gp120 and gp41, that are formed gradient sedimentation, polyacrylamide gel electrophoresis, gradient sedimentation, polyacrylamide gel electrophoresis, and chemical cross-linking, we show that gp160 is synthesized as a monomer and subsequently forms stable homodimers. The molecule remains dimeric after cleavage to gp120/gp41 but is less stable to detergent solubilization and centrifugation. Analysis of wild-type and mutated env proteins indicated that interactions between the ectodomain regions of adjoining gp41 subunits are important for dimer formation and stability. A higher-order oligomeric form was also recovered, probably a tetramer consisting of two noncovalently associated dimers. The proposed subunit composition of the HIV-1 env protein is identical to that previously observed for the paramyxovirus envelope proteins F and HN.